Double aortic arch in a newborn with congenital diaphragmatic hernia and tracheoesophageal fistula. (28th April 2014) - Chiu, Joanne S.; Glickstein, Julie; Shah, Amee
Abstract Congenital heart disease is associated with congenital diaphragmatic hernia, but diagnosis by echocardiography can be difficult. We present the unusual case of a patient with a double aortic arch and congenital diaphragmatic hernia diagnosed using cardiac magnetic resonance imaging.